CRISPR/Cas9-mediated mutation in auxin efflux carrier OsPIN9 confers chilling tolerance by modulating reactive oxygen species homeostasis in rice - Xu, Huawei; Yang, Xiaoyi; Zhang, Yanwen; Wang, Huihui; Wu, Shiyang; Zhang, Zhuoyan; Ahammed, Golam Jalal; Zhao, Chunzhao; Liu, Hao (Frontiers in Plant Science, 2022)
Phytohormone auxin plays a vital role in plant development and responses to environmental stresses. The spatial and temporal distribution of auxin mainly relies on the polar distribution of the PIN-FORMED (PIN) auxin efflux carrier. In this study, we dissected the functions of OsPIN9, a monocot-specific auxin efflux carrier gene, in modulating chilling tolerance in rice. The results showed that OsPIN9 expression was dramatically and rapidly suppressed by chilling stress (4℃) in rice seedlings. The homozygous ospin9 mutants were generated by CRISPR/Cas9 technology and employed for further research. ospin9 mutants roots and shoots were less sensitive to 1-naphthaleneacetic acid (NAA) and N-1-naphthylphthalamic acid (NPA), indicating the disturbance of auxin homeostasis in the ospin9 mutants. The chilling tolerance assay showed that ospin9 mutants were more tolerant to chilling stress than wild-type (WT) plants, as evidenced by increased survival rate, decreased membrane permeability and reduced lipid peroxidation. However, the expression of well-known C-REPEAT BINDING FACTOR (CBF)/DEHYDRATION-RESPONSIVE ELEMENT-BINDING PROTEIN 1 (DREB)-dependent transcriptional regulatory pathway and Ca2+ signaling genes were significantly induced only under normal conditions, implying that CBF/DREB-dependent pathway and Ca2+ signaling pathway probably play a minor role in regulating chilling tolerance of ospin9 mutants under chilling conditions. Histochemical staining of reactive oxygen species (ROS) by 3’3-diaminobenzidine (DAB) and nitroblue tetrazolium (NBT) showed that ospin9 mutants accumulated more ROS than WT at the early stage after chilling treatment, while less ROS was observed at the later stage of chilling treatment in ospin9 mutants. Consistently, antioxidant enzyme activities, including catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD), improved significantly during the early chilling treatment, while keep similar to WT at the later stage of chilling treatment, implying that the enhanced chilling tolerance of ospin9 mutants is mainly attributed to the earlier induction of ROS and the improved ROS scavenging ability at the subsequent stages of chilling treatment. In summary, our results strongly suggest that the OsPIN9 gene regulates chilling tolerance by modulating ROS homeostasis in rice.